Clinical Characteristics, Organ Dysfunctions and Outcomes of Scrub typhus from South India. (March 2022) - Chunduru, K.; Mohammed, S.K.; M, M.; Saravu, K.
Abstract : Purpose: To study the clinical characteristics, severity of infection and outcomes among scrub typhus patients. Methods & Materials: A prospective cohort study was performed on patients diagnosed with Scrub typhus based on IgM ELISA or eschar, presenting to a tertiary care hospital in South India during August 2019 – March 2021. Clinical, epidemiological, laboratory parameters and in hospital outcomes of patients were captured in a proforma. Predefined severity criteria which considers cardiovascular, respiratory, central nervous system, renal, hepatic, and haematological parameters was used to segregate patients into severe and non-severe groups. Results: A total of 132 Scrub typhus patients positive by IgM ELISA or eschar were enrolled in the study. Males were 70 (53%) females were 62 (47%), mean age was 49.20 ±14.07. Cases were reported during August to March during both years. Majority of patients were housewives 47 (35.6%) followed by farmers 42 (31.8%). Based on severity criteria 78 (59%) patients were segregated into severe group and 54 (41%) to non-severe group. Eschar was present in 11 (14.1%) severe and 9 (16.6%) non-severe patients. Laboratory parameters such as platelet count, total bilirubin, direct bilirubin, and serum creatinine were deranged among severe patients, with statistical significance. Fifty-six (71.7%) patients had liver dysfunction (Total bilirubin >2mg/dL) followed by 30 (38.4%) patients with respiratory involvement (<92% SpO2 requiring oxygen supplementation). Nine (11.5%) patients had CNS manifestations. Intensive care admission 46 (59%), ventilation 26 (33.3%), ionotropic support 15 (19.2%), dialysis 8 (10.3%) and median length of hospitalisation in days 8 (7, 11) were higher among severe patients with statistical significance. Six patients (2 succumbed + 4 discharged in critical condition) had a poor outcome. Conclusion: Scrub typhus is an important cause of AFI in South India, which often leads to severity and organ dysfunction in tertiary care settings. Hepatic dysfunction was the major organ involvement. Scrub typhus as a possible cause of meningitis, should be kept in differential diagnosis in endemic settings. High clinical suspicion, robust severity criteria and diagnostic assays are required for early identification. Timely initiation of doxycycline or azithromycin orally or intravenously based on severity of infection can lead to improved outcomes.